Eugen Doga și realitățile culturale la Biblioteca de Arte „Tudor Arghezi” - MOLDOVANU, Anastasia (BIBLIOPOLIS, 2026)
Composer Eugen Doga has been a constant supporter of libraries, contributing significantly to the development of their collections. The Tudor Arghezi Arts Library has benefited from his generous donations, thanks to his deep understanding of the needs of a specialized collection. During the National Renaissance, when libraries redirected their acquisitions toward Romanian-language materials, Eugen Doga’s contribution had a major impact: his donations (dictionaries, encyclopedias, art albums, scores, theoretical works, CDs and DVDs, often with autographs) helped align the library’s profile with European standards. Even today, these carefully selected resources remain valuable reference points within the Tudor Arghezi Arts Library’s collections.